2007
DOI: 10.1016/j.jpain.2007.02.433
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1A Safety Assessment of Intravenous Amitriptyline

Abstract: Amitriptyline potently blocks the persistently open Na+ channels, which are known to be instrumental in various pain states. As this occurs at very low plasma concentrations, a single preoperative intravenous infusion of amitriptyline could provide long-lasting pain relief and decrease the incidence of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This dosage has been demonstrated to be safe for intravenous administration in a recent clinical study. 26 In this study, preoperative intravenous infusion of amitriptyline over 1 hour appeared to be safe at a dose of 50 mg as assessed by QTc interval, adverse effects monitoring, and measurements of plasma levels of amitriptyline and nortriptyline. Similarly, our experience from treating patients with a wound chamber confirms the observation that high dosages of antibiotics can be administered topically without systemic toxicity.…”
Section: Discussionmentioning
confidence: 72%
“…This dosage has been demonstrated to be safe for intravenous administration in a recent clinical study. 26 In this study, preoperative intravenous infusion of amitriptyline over 1 hour appeared to be safe at a dose of 50 mg as assessed by QTc interval, adverse effects monitoring, and measurements of plasma levels of amitriptyline and nortriptyline. Similarly, our experience from treating patients with a wound chamber confirms the observation that high dosages of antibiotics can be administered topically without systemic toxicity.…”
Section: Discussionmentioning
confidence: 72%
“…Amitriptyline is sometimes used as an alternative following lidocaine. 20 Herein, we report detailed clinical and genetic investigation of a family with PEPD caused by a novel mutation in the SCN9A gene; in vitro electrophysiological evidence of pathogenicity; and effects of amitriptyline and cold exposure both at the clinical and electrophysiological levels.…”
Section: Pain Medicinementioning
confidence: 99%
“…Alternatively, AM is a potent local anesthetic with longer effect compared with bupivacaine 9 . The analgesic effect of AM is most likely caused by blocking of Na + channels 8 . So therefore, we aimed to evaluate the analgesic effect of AM mucoadhesive tablet as a topical dosage form.…”
Section: Buccal Analgesic Efficiencymentioning
confidence: 99%
“…The analgesic effect of tricyclic antidepressant medicines seems unrelated to their antidepressant action as the doses used for analgesia are lower than those considered effective in the treatment of depression [1][2][3][4][5][6][7] . The analgesic effect of AM is almost certainly due to blocking of Na + channels 8 . Further experimentation has shown that AM is indeed a potent local anesthetic with longer effect compared with bupivacaine 9 .…”
Section: Introductionmentioning
confidence: 99%